Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have a sequence defined by the relation $$x_{n+1} = \alpha x_n + (1-\alpha)x_{n-1}$$ for $n\geq 1$, and I want to find the limit in terms of $\alpha , x_0,x_1$. I tried to do this by setting up a matrix equation, but that didn't work out, so I took a peek at the solution. It said that I first needed to realize that $x_n-x_{n-1} = (\alpha - 1)(x_n-x_{n-1})$. I've tried playing around with the initial relation algebraically, but I'm stuck as to how to get this second relation below.

Any pointers would be greatly appreciated!

share|improve this question
    
The solution is wrong (or you copied it incorrectly). Try looking at $x_{n+1}-x_n$. –  David Mar 26 at 23:58
    
Solve the recurrence relation and then try to find the limit. –  Mhenni Benghorbal Mar 26 at 23:59
    
@David Ah I see! $x_{n+1} - x_n$ yields the term on the RHS. –  joe Mar 27 at 0:02

3 Answers 3

The characteristic equation is $$r^2-\alpha r+(\alpha-1)=0,\qquad \Delta=\alpha^2-4\alpha+4=(\alpha-2)^2$$ and its roots are $$r_{1}=\alpha-1\quad;\quad r_2=1$$ hence if $\alpha\ne2$: $$x_n=a(\alpha-1)^n+b$$ and if $\alpha=2$: $$x_n=an+b$$ and $a$ and $b$ are determined using $x_0$ and $x_1$.

share|improve this answer
    
This is the most procedural method, +1. –  Nameless Mar 27 at 0:56

Subtract $x_n$ from both sides, to get $$x_{n+1}-x_n=(\alpha-1)x_n+(1-\alpha)x_{n-1}$$ Then collect to get $$x_{n+1}-x_n=(\alpha-1)(x_n-x_{n-1})$$

It's not exactly the hint, the index is off by one. However the conclusion is the same -- if $0< \alpha <1$, then the limit of $(\alpha-1)^n$ is zero.

share|improve this answer

Use generating functions, no creativity involved... write: $$ x_{n + 2} = \alpha x_{n + 1} + (1 - \alpha) x_n $$ Define $X(z) = \sum_{n \ge 0} x_n z^n$, multiply the recurrence by $z^n$, add over $n \ge 0$, recognize some sums: $$ \frac{X(z) - x_0 - x_1 z}{z^2} = \alpha \frac{X(z) - x_0}{z} + (1 - \alpha) X(z) $$ Solve and write as partial fractions: $$ X(z) = \frac{x_1 + (1 - \alpha) x_0}{2 - \alpha} \cdot \frac{1}{1 - z} - \frac{x_1 - x_0}{2 - \alpha} \cdot \frac{1}{1 + (1 - \alpha) z} $$ This is just two geometric series: $$ x_n = \frac{x_1 + (1 - \alpha) x_0}{2 - \alpha} - \frac{x_1 - x_0}{2 - \alpha} \cdot (-1)^n (1 - \alpha)^n $$ As presumably $0 < \alpha < 1$, this tells you it converges and what the limit is.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.